ANALYSIS OF ACCOUNTING INFORMATION TOWARDS STOCK RETURN IN FOOD AND BEVERAGE INDUSTRY LISTED ON INDONESIA STOCK EXCHANGE FOR THE PERIOD OF 2010-2014 - Joane, Meidisa; Pratama, Indra (Emerging Markets : Business and Management Studies Journal, 2015)
This study investigates the correlations of the accounting information: current ratio, debt-to-equity ratio, total assets turnover, price-to-earnings ratio, and firm size towards stock return. This is to respond the economic condition and improvement of Asian market towards the global economy, and increasing consumer spending in food and beverage in Indonesia. Some previous studies found that there is a correlation between the variables and the stock return. This study then reveals a significant correlation of current ratio, debt-to-equity ratio, total asset turnover, and firm size when they are put as a single variable, towards the stock return. However, the price-to-earnings ratio is found to have an significant correlation towards the stock return, and so do all the accounting information as independent variables when combined in multiple regression model.